2023
DOI: 10.1039/d2np00063f
|View full text |Cite
|
Sign up to set email alerts
|

Natural products of pentacyclic triterpenoids: from discovery to heterologous biosynthesis

Abstract: Natural products of pentacyclic triterpenoids: from their discovery and biosynthetic pathways to their heterologous biosynthesis in plant chassis and microbial cell factories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 342 publications
(319 reference statements)
0
49
0
Order By: Relevance
“…the key enzymes for ginsenoside biosynthesis from Pg , including CYP450s, UGTs, and oxidosqualene cyclases (OSCs), were introduced to achieve ginsenosides in yeasts. Three genes have been found from multiple sources, such as higher plants Arabidopsis thaliana , Sorghum bicolor , Solanum lycopersicum , Glycine max , and Oryza sativa [ 67 , 68 ]. However, Pg has been demonstrated as the most important source for producing ginsenosides with high efficiency.…”
Section: Ginsenoside Biosynthesis In Engineered Microorganismsmentioning
confidence: 99%
“…the key enzymes for ginsenoside biosynthesis from Pg , including CYP450s, UGTs, and oxidosqualene cyclases (OSCs), were introduced to achieve ginsenosides in yeasts. Three genes have been found from multiple sources, such as higher plants Arabidopsis thaliana , Sorghum bicolor , Solanum lycopersicum , Glycine max , and Oryza sativa [ 67 , 68 ]. However, Pg has been demonstrated as the most important source for producing ginsenosides with high efficiency.…”
Section: Ginsenoside Biosynthesis In Engineered Microorganismsmentioning
confidence: 99%
“…The carbocation‐go stage has been well described, [7,14] and the carbocation‐return stage is closely associated with PT formation, which requires further study. A high number of β ‐amyrin synthases found in nature seems to favor the formation of β ‐amyrin [1] . Among the putative intermediates in Figure 1e (state E–J), more rearrangement mechanisms are involved in the formation of friedelin, which we referred to as the “CSR mechanism,” involving intermediates and catalytic mechanisms that remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Pentacyclic triterpenoids (PTs) are widely distributed in higher plants and exhibit a wide range of bioactivities, such as antitumor, [1] anti-inflammatory, [2] and antiviral activity. [3] Recent studies have identified PTs as vaccine adjuvants to boost the immune response.…”
Section: Introductionmentioning
confidence: 99%